2019
DOI: 10.1158/1055-9965.epi-18-1194
|View full text |Cite
|
Sign up to set email alerts
|

Use of Statin Medications Following Diagnosis in Relation to Survival among Women with Ovarian Cancer

Abstract: Background: It has been suggested that the likelihood of survival among women with ovarian cancer could be increased by postdiagnosis statin use. This study examines the potential association between postdiagnosis statin use and cancer-specific mortality among women with ovarian cancer.Methods: This cohort study used SEER-Medicare data on women 66 years of age diagnosed with ovarian cancer during 2007 to 2012 who were enrolled in Medicare parts A, B, and D during the year after diagnosis. Statin use was define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…After the study of the finally enrolled 24 articles, two other studies were excluded because the effect size of statin on the incidence or mortality of OC had not been calculated or not been reported in the study and four studies were found as being irrelevant to my research according to the information of the full texts of the articles. Eighteen articles were selected for final analysis, of which ten articles were included for the assessment of the relationship between statin use and the risk of developing OC [ 11 , 12 , 16-18 , 22 , 23 , 32-34 ], and nine articles for the relationship between post-diagnosis statin consumption and OC mortality [ 11 , 13-15 , 19-21 , 35 , 36 ]. It should be noted that Lavie et al study [ 11 ], addressed both the risk of incidence and mortality of from OC ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After the study of the finally enrolled 24 articles, two other studies were excluded because the effect size of statin on the incidence or mortality of OC had not been calculated or not been reported in the study and four studies were found as being irrelevant to my research according to the information of the full texts of the articles. Eighteen articles were selected for final analysis, of which ten articles were included for the assessment of the relationship between statin use and the risk of developing OC [ 11 , 12 , 16-18 , 22 , 23 , 32-34 ], and nine articles for the relationship between post-diagnosis statin consumption and OC mortality [ 11 , 13-15 , 19-21 , 35 , 36 ]. It should be noted that Lavie et al study [ 11 ], addressed both the risk of incidence and mortality of from OC ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In nine meta-analysis studies, a total of 14,382 participants were enrolled based on our inclusion criteria. Among the included studies [ 11 , 13-15 , 19-21 , 35 , 36 ], seven studies were cohort with total sample size of 8,630 cases with OC [ 13-15 , 19 , 20 , 35 , 36 ] and two studies were case-control studies with total sample size of 210 cases with OC [ 11 , 21 ]. The studies had been published between 2008 and 2019.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides prevention of cardiovascular disease, statins have therapeutic effects in several ovary and uterus related diseases, such as polycystic ovary syndrome 4 , ovarian cancer 5 , endometrial cancer 6 , uterine fibroids 7 , and endometriosis 8 . But meanwhile, concerns have been raised about potential toxicity for ovary and uterus associated with statin use.…”
Section: Ovary and Uterus Related Adverse Events Associated With Statmentioning
confidence: 99%